Islamic Discourse and Baduy in Tanah Ulayat Kanekes: Contestations and Connections - Salma Qowiyatun Naziah; Holy Rafika Dhona (Asian Journal of Media and Communication, 2021)
The Cicakal Girang village, known as the village where the Muslim Baduy lives, has different religious practices from the Baduy. Obedience to Baduy customs is very loose in this village, which the Baduy indigenous community permits. This study investigates the cultural discourse producing the Cicakal Girang village and the reproduction of such discourse as well. The empirical data were collected through fieldwork and analyzed with the cultural discourse analysis method. This study finds that the Cicakal Girang and its Islamic activities practice the existing discourse system, namely the Cicakal Girang as a place of the 'penghulu ratu’ (the queen) of the Baduy community. Such discourse situates the Cicakal Girang as a connection space for the Baduy community with the outside world. It is reproduced in the interaction between Cicakal Girang and the Baduy community. Keywords: Baduy, Cicakal Girang, communication geography, cultural discourse analysis